2013
DOI: 10.3109/00365521.2013.870597
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypercoagulable disorders in inflammatory bowel disease

Abstract: OBJECTIVE. Inflammatory bowel disease (IBD) can be associated with hypercoagulable disorders. Aim of this single-center, prospective study was an in-depth evaluation of acquired hypercoagulable states in IBD patients. METHODS. A total of 110 patients with Crohn's disease (CD) (aged 19-69; mean 40.5, median 38.5 years), 43 with ulcerative colitis (UC) (aged 17-72; mean 42, median 36 years), and 30 controls were enrolled. Full blood count, serum C-reactive protein (CRP), proteins C and S, activated protein C (AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…The American College of Gastroenterology and the European Crohn's and Colitis Organisation agree that all hospitalized patients with IBD, especially those with colitic symptoms, should be considered for prophylactic anticoagulation . This may be related to a hypercoagulable state in patients with IBD in both the local and systemic circulation and may be associated with increased production of thrombin, impaired fibrinolysis and increased platelet aggregation …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The American College of Gastroenterology and the European Crohn's and Colitis Organisation agree that all hospitalized patients with IBD, especially those with colitic symptoms, should be considered for prophylactic anticoagulation . This may be related to a hypercoagulable state in patients with IBD in both the local and systemic circulation and may be associated with increased production of thrombin, impaired fibrinolysis and increased platelet aggregation …”
Section: Discussionmentioning
confidence: 99%
“…The risk of arterial and venous thrombotic events is increasing in both adult and pediatric patients with inflammatory bowel disease (IBD) . Cerebral venous thrombosis (CVT) is a rare but devastating complication of IBD that is estimated to occur in 0.5–7.5% of patients .…”
Section: Introductionmentioning
confidence: 99%
“…Damage to the vascular wall activates the haemostatic system, triggering thrombus formation and inflammatory infiltration 9. Studies comparing patients with active IBD, inactive IBD and normal controls have revealed an upsurge in the levels of procoagulant factors, and decrease in anticoagulant factors in active disease 9 11. As anticoagulant mechanisms serve to dampen the inflammatory process, their suppression leads to a vicious circle of further inflammation and increased prothrombotic tendencies.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the literature, there is no definitive explanation for this. Nevertheless, (1) reported activation of NF-κβ signalling cascade by S100A4 (31), (2) suggestion that the NF-κβ signalling cascade may be the central mediator of gastrointestinal inflammation in IBD and malignancies (40), (3) known properties of metastatin -being a mediator of metastatic processes (27), (4) and known association of colorectal carcinoma with IBD (43) are compatible with our observation of higher levels of serum S100A4 in IBD patients with colonic involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Serum markers of inflammation -decreased thrombocyte volume and/or elevated thrombocyte count, white blood cell count, erythrocyte sedimentation rate and C-reactive protein -help to assess activity of IBD, mainly (2)(3)(4)(5)(6)(7). Whichever antibody or combination of antibodies associated with IBD, including serum ASCA (anti-Sacharomyces cerevisiae antibodies), ABBA (anti-brush border antibodies), anti-I2 (antibodies to DNA fragments of Pseudomonas fluorescens), Anti-CBir1 (antibodies to CBir1 flagellin), anti-GP2 (antibodies to glycoprotein 2), anti-OmpC (anti-outer membrane protein C antibodies), pANCA (perinuclear anti-neutrophil cytoplasmic antibody), different levels of serum IgG1 and IgG2, ALCA (anti-laminaribioside carbohydrate antibodies), ACCA (anti-chitobioside carbohydrate antibodies) are present (8)(9)(10)(11)(12)(13)(14)(15), their role to establish the definitive diagnosis of IBD/UC/CD is still supportive only.…”
Section: Introductionmentioning
confidence: 99%